2013
DOI: 10.1159/000351165
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Ovarian Cystectomy versus Fenestration/Coagulation or Laser Vaporization for the Treatment of Endometriomas: A Meta-Analysis of Randomized Controlled Trials

Abstract: Aim: To compare outcomes after laparoscopic ovarian cystectomy versus fenestration/coagulation or laser ablation for the treatment of endometriomas. Methods: Studies were identified by searching the PubMed, EMBASE, SCOPUS, and Cochrane Central Register of Controlled Trials databases using the terms ovarian, endometrioma or endometriosis, cystectomy, fenestration, coagulation, laser, and ablation or vaporization. The outcomes of interest were recurrence of signs/symptoms and endometrioma, reoperation, pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 23 publications
0
36
0
2
Order By: Relevance
“…Laparoscopic cystectomy is associated with lower recurrence rates compared to fenestration and coagulation/laser vaporization [42]. In our study, we noted that recurrence of endometrioma following prior cystectomy was not associated with lower pregnancy rates to those patients with no recurrence following cystectomy or patients with transvaginal USG-based diagnosis.…”
Section: Discussionmentioning
confidence: 51%
“…Laparoscopic cystectomy is associated with lower recurrence rates compared to fenestration and coagulation/laser vaporization [42]. In our study, we noted that recurrence of endometrioma following prior cystectomy was not associated with lower pregnancy rates to those patients with no recurrence following cystectomy or patients with transvaginal USG-based diagnosis.…”
Section: Discussionmentioning
confidence: 51%
“…Laparoscopic surgery is currently the first choice for the diagnosis and treatment of infertility in patients with endometriosis [6], although researchers have found some genes suitable for diagnostic quantitative RT-PCR for endometriosis in the peripheral blood [7,8]. A meta-analysis of two trials has demonstrated the advantage of laparoscopic surgery for early-stage endometriosis compared with diagnostic laparoscopy in regard to ongoing pregnancy at 20 weeks (odds ratio, 1.64; 95% confidence interval: 1.05-2.57) [9].…”
Section: Discussionmentioning
confidence: 99%
“…The current data suggest that cystectomy for endometrioma cannot prevent postoperative ovarian cancer. As for the surgical procedure for endometrioma, Dan and Limin [22] showed the results of a meta-analysis that cystectomy provided better outcomes than fenestration/coagulation or laser ablation regarding the recurrence of symptoms and endometrioma. In the 16 patients in whom cancer emerged after hormonal treatment, shown in table 2, ovarian cancer was not found during medical treatment.…”
Section: Discussionmentioning
confidence: 99%